Rapid identification of polyamides using direct analysis in real time mass spectrometry. (27th February 2020) - Abe, Yutaka; Ackerman, Luke K.; Mutsuga, Motoh; Sato, Kyoko; Begley, Timothy H.
Abstract : Rationale: Polyamide (PA) is the generic name of polymers synthesized by linking monomers via amide bonds, and various types of PAs with different monomer compositions are known. Distinguishing PA polymers is useful in directing monomer residual testing, product testing, and reverse engineering, but is analytically challenging and cumbersome. To simplify this, we explored the applicability of direct analysis in real time mass spectrometry (DART‐MS) for screening PA polymers. Methods: A DART ion source coupled to a quadrupole Orbitrap (high‐resolution (HR) mass spectrometer) was employed for this study. Ten types of PA polymers and four retail samples were evaluated. The DART‐HRMS data for these samples, as well as the DART‐MS/MS (MS 2 ) data for PA6 and PA66, were obtained, and their repeatability was assessed across days/calibrations, operators, and equipments. Results: Ions corresponding to the cyclic or linear monomers and oligomers of each PA polymer were detected in each DART‐HR mass spectrum. Although similar DART‐HR mass spectra were obtained for PA6, PA66, and PA6/PA66 (polymer blends of PA6 and PA66), their DART tandem mass spectra were completely different. The analysis was repeatable, and nearly identical DART tandem mass spectra were obtained on different days, by different operators, and with different equipment. This technique was successfully applied to commercially available samples. Conclusions: Ten types of PA polymers were distinguished using DART‐HRMS and DART‐MS 2, and their identification using these techniques was straightforward as the characteristic ions for each PA polymer were identified and detected. Furthermore, the spectra were obtained rapidly. Therefore, DART‐HRMS can be considered an efficient screening technique for the rapid identification and differentiation of PA polymers.